Implementation of Village Governance on Public Services in Langensari Village - Rachmawati, Emi; Arifin, Farid; Adimanggala, Rangga Muharram; Malik, Hasan Abdul; Amarullah, Karim; Amanda, Jesica Clarisa; Al Bilqis, Valina Mutiara Tsabbit; Agisty, Yulina; Anggraieni, Lenniy; Naura Sari, Niswa Afifah (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This research explains public services in Langensari Village by emphasizing aspects of accountability, transparency, effectiveness and efficiency. The focus includes planning and development to advance village welfare. In regional development, the government emphasizes the bottom-up system, namely villages. Village governance is a form of government administration in realizing development in the village. In this case, creating good governance can improve public services in the village which can support the performance of village officials in serving the community. Optimal service must always be provided by regional government officials, especially village governments. That one of the goals of village regulation is to improve public services for service providers as well as possible is one of the performance results that village governments can carry out to achieve the goals set out in national service standards, namely service quality. Optimal public services can create village government that is professional, efficient and effective, open and responsible, or good governance. This research explains public services in Langensari Village by emphasizing aspects of accountability, transparency, effectiveness and efficiency. The focus includes planning and development to advance village welfare. In regional development, the government emphasizes the bottom-up system, namely villages. Village governance is a form of government administration in realizing development in the village. In this case, creating good governance can improve public services in the village which can support the performance of village officials in serving the community. Optimal service must always be provided by regional government officials, especially village governments. That one of the goals of village regulation is to improve public services for service providers as well as possible is one of the performance results that village governments can carry out to achieve the goals set out in national service standards, namely service quality. Optimal public services can create village government that is professional, efficient and effective, open and responsible, or good governance.